Respons Strategis Perusahaan terhadap Ancaman Dinamika Kompetitif : Pendekatan Studi Literatur - Azmi Talitha Gani; Cantika Dewi Apriyani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The increasingly dynamic and competitive business environment requires companies to respond strategically to various external threats. This study aims to examine the strategic responses adopted by companies in facing competitive dynamics through a literature review approach. The method used is a systematic review of scholarly articles published in the last five years. The findings indicate that companies implement various strategies—such as product innovation, strategic alliances, and organizational restructuring—as responses to competitive pressures. This study contributes to a better understanding of how companies can survive and grow amidst intense market competition.